2006
DOI: 10.1002/gps.1733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the home help service and its impact on the informal caregiver's burden of dependent elders

Abstract: These data show the need to extend the services delivered by the HHS and the duration of care, address the caregiver's need for psychological care, and look at potentially modifiable variables in the care context when designing prevention and psychosocial intervention programmes to lessen the informal caregiver's burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 17 publications
3
49
0
5
Order By: Relevance
“…Several investigations have proposed the suitability of combining both types of programs, the respite services and psychoeducational programs, to deal with the excessive burden of the informal caregivers of dependent people (Carretero et al, 2007;Garcé s et al, in press). Specifically in Spain, the use of HHS is an important social resource which exists in the network of Spanish Public Social Services, which would be useful to provide respite to the caregivers of dependent people for their care tasks, at the same time, it allows the dependent person to remain in their home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigations have proposed the suitability of combining both types of programs, the respite services and psychoeducational programs, to deal with the excessive burden of the informal caregivers of dependent people (Carretero et al, 2007;Garcé s et al, in press). Specifically in Spain, the use of HHS is an important social resource which exists in the network of Spanish Public Social Services, which would be useful to provide respite to the caregivers of dependent people for their care tasks, at the same time, it allows the dependent person to remain in their home.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this, some researches have concluded on the relevance to use the following strategies in the design of the social and health care policies to maximize the efficiency of the HHS to relieve the excessive burden (Carretero et al, 2006(Carretero et al, , 2007Garcé s et al, in press): (a) expanding the type of services provided and the duration of the care provision by the HHS in order to allow the caregiver to rest in a sufficient way and decrease his/her excessive burden levels; (b) increasing the coverage of the needs for the main caregiver, and especially the psychological care requirements by means of the inclusion of psycho-educational programs to alleviate the emotional discomfort of the informal caregivers and provide them with skills and strategies to face the challenge of caregiving. In our context, it is especially important to focus this type of programs to the female population, insofar as recent data indicates that in 84% of the cases in Spain, the informal care to dependent senior citizens is assumed by a woman (IMSERSO, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score, ranging from 0 to 88, 22 items with five answers (0 to 4), amounts to a total burden score where a high score is equivalent to a high burden level. A previous study carried out with this sample of caregivers has shown that this scale is comprised by three factors, which are: negative consequences of caregiving (Factor 1), feelings of incompetence (Factor 2) and negative relationships (Factor 3) (Carretero et al, 2007). The minimum score for the three factors is 0 (never) and the maximum scores are 48, 20 and 12 (very often), respectively.…”
Section: Variables and Instrumentsmentioning
confidence: 91%
“…Of the entire sample of dependent persons, 153 had an informal caregiver who attended them: 117 users of HHS and 36 non-users of this service. Preliminary analysis has demonstrated that there are no statistically significant differences between the user and non-user caregivers of the HHS neither in their overall burden level nor in the sociodemographic characteristics of the dependent persons and their caregivers between the two groups of users (Carretero et al, 2007). For this reason, a total sample of informal caregivers (n = 153) and dependent senior citizens (n = 296) was taken for this work.…”
Section: Sample and Data Collectionmentioning
confidence: 99%